Efforts to Increase the Effectiveness of Google Forms as a Tool for Reporting Occupational Accidents and Dangerous Events at Paru Manguharjo Hospital Madiun - Sumiati; Yenny Puspitasari; Ratna Wardani (Universitas STRADA Indonesia, 2025)
Patient safety is a topic that has been the subject of much discussion in recent decades. Patient safety is defined as failure to complete what has been planned or achieving something using the wrong means. In general, this community service is carried out to identify strategies in making efforts so that the reporting of occupational accidents and dangerous events at the Manguharjo Lung Hospital Madiun, knowing the variables that are strengths, weaknesses, opportunities and threats and to find out the strategies that can be taken by the Manguharjo Lung Hospital Madiun. The assessment or identification of problems in this residency report uses a Fishbone diagram. Based on the assessment that has been carried out using the SWOT kite diagram to prioritize strategies to be implemented to overcome existing problems, the intervention plan for this residency is the formation of a strategy in making efforts to report work-related accidents and dangerous events, one of which is by optimizing the google form at the Manguharjo Lung Hospital Madiun.